2019
DOI: 10.5958/0976-5506.2019.00358.9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Risk Assesment of Crystalline Silica Exposure in Ceramics Industry

Abstract: Crystalline silica can be found in Ceramics Industry. Ceramics are basically made of clay, feldspar and silica sand. Ceramics manufacturing process starts from the processing of materials, forming, drying, burning and gazing. Crystalline silica consists of three types of quartz, tridymite and cristobalite which are distinguished by their forming temperature. Crystaline silica dust is very dangerous for health workers are exposed continuously it can cause a silicosis. Prevention and control efforts can be done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…According to R. Iler, quartz dust causes silicosis and pulmonary fibrosis [7]. The most dangerous are the particles of solid samples of crystalline silica with a particle size of 0.2-7 microns [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…According to R. Iler, quartz dust causes silicosis and pulmonary fibrosis [7]. The most dangerous are the particles of solid samples of crystalline silica with a particle size of 0.2-7 microns [8,9].…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian yang dilakukan di Amerika Serikat menunjukkan bahwa ada 3600-7300 kasus silikosis per tahun pada 1987-1963. 4 Menurut NIOSH, polutan atmosfer seperti partikulat mampu menghasilkan efek buruk pada beberapa kondisi pajanan dan dosis sepanjang waktu. 5 Debu keramik yang dihasilkan oleh proses panas di pabrik-pabrik keramik biasanya dalam…”
Section: Pendahuluanunclassified
“…The research result (Sahri et al, 2019) showed that 42.6% of respondents have an unsafe risk level of exposure to c-silica dust and potential health problems due to c-silica dust. Based on the estimated calculation of chronic exposure risk, the risk level tends to increase over the next 20 years.…”
Section: Introductionmentioning
confidence: 96%